A RESEARCH ON DETERMINING THE REASONS OF HEDONIC PURCHASE IN ONLİNE SHOPPING (Third Sector Social Economic Review, 2020)
In this study, which was carried out to determine the reasons for hedonic purchases in online shopping, consumers were asked whether they shop online primarily, and the research was not continued with consumers who did not shop online. The online shopping consumers participating in the study were asked about 5 dimensions (adventure, value, role, information, relaxation) regarding demographic characteristics, frequency of online shopping and the adaptation of the Hedonic Purchasing Scale developed by Arnold and Reynolds (2003) for online purchasing. Approximately 394 participants were reached in the research conducted through the face-to-face survey method, and 310 of them continued their research with this number since they shop online. As a result of the study, a relationship was found between the frequency of orders placed online and hedonic purchases. “Role” dimension and “value” dimension are among the reasons that push consumers to buy online. When consumers are making hedonic purchases, they give more importance to these two dimensions rather than adventure, relaxation and knowledge dimensions.
Keywords: Online Shopping; Hedonic Purchase; Internet